Hinweise auf eine Überfischung grönländischer Grundfischbestände - Rätz, Hans-Joachim (1996)
At present, the severe decline of the fishery off Greenland is being discussed controversially. In contrast to overfishing, climate changes and emigration are itemized causal. Available German data on commercial catches and research cruises are presented for clarification. A few years after the beginning of heavy exploitation during the early sixties, the stocks of cod, golden and beaked redfish reflected a significant rejuvenescence based on catch analysis. Regular scientific surveys• for stock assessment purposes commenced in 1982 when the productivity of the stocks was already adversely affected due to low spawning stocks and extremely irregular recruitment. From this point of view, the results of the latest survey in 1995 showing stagnant fish biomass at record low level since 1991 are not surprising. The status of the cod stock is still considered severely depleted. Taking the high abundance of juvenile redfish into account, recovery of the groundfish stocks is unlikely in short term and depends on the non-predictable recruitment only.